Greenpreneur – Membangun Bisnis dari Limbah Plastik: Kepedulian terhadap Lingkungan Hidup dan Ekonomi Masyarakat - Yenni Elfiza Abbas; Deni Gustiawan; Rahmat Prayoga; Indra Pradana; Gustofan Mahmud; Basyiruddin Basyiruddin; Mulyadi Mulyadi (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
The Community Service Activity was held on June 20, 2024, at the Institut Bisnis dan Komunikasi Swadaya - Jakarta, with the theme "Greenpreneur: Building Business from Plastic Waste," aimed to enhance participants' understanding and awareness of environmental management, specifically through the utilization of plastic waste. This initiative focuses on developing business opportunities based on MSMEs by transforming plastic waste into valuable products. The program included several subthemes, such as strategies for managing superior human resources for MSMEs, calculating production costs for flower arrangements, processing plastic waste into handicrafts as a foundation for new entrepreneurship for academic communities, calculating income tax for MSMEs that produce recycled plastic, and training on making flowers from used plastic bottles. Through this activity, participants gained insights into environmental awareness, plastic waste processing techniques, and skills for starting independent businesses. This activity successfully improved the competencies of students and the community in environmentally-based entrepreneurship, enhancing their courage and skills to start and manage MSMEs effectively.